2001
DOI: 10.1016/s0022-5347(05)66435-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Bilateral Synchronous Nephrectomy for Autosomal Dominant Polycystic Kidney Disease: The Initial Experience

Abstract: Synchronous bilateral retroperitoneal laparoscopic nephrectomy for giant symptomatic adult polycystic kidney disease is feasible, safe and efficacious, and can be performed either before or after renal transplantation. Compared to open surgery, the laparoscopic approach results in significantly shorter hospital stay, decreased morbidity and quicker recovery. Laparoscopy is currently our technique of choice in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 15 publications
1
61
0
3
Order By: Relevance
“…Future possibilities can be a laparoscopic approach at the same operation. 7 The operative time increased a mean of 70 minutes, the need for fluids and blood products was greater, but the hemodynamic parameters were comparable at the moment of reperfusion, allowing similar short-and long-term outcomes for grafts and patients. There was only one surgical (urologic) complication in the nephrectomy group, allowing us to conclude that this is a safe procedure.…”
Section: Discussionmentioning
confidence: 97%
“…Future possibilities can be a laparoscopic approach at the same operation. 7 The operative time increased a mean of 70 minutes, the need for fluids and blood products was greater, but the hemodynamic parameters were comparable at the moment of reperfusion, allowing similar short-and long-term outcomes for grafts and patients. There was only one surgical (urologic) complication in the nephrectomy group, allowing us to conclude that this is a safe procedure.…”
Section: Discussionmentioning
confidence: 97%
“…As disadvantages of this method we may include the need to reposition the patient for access to the kidney on the opposite side, and the incision for the removal of the kidney. 3 In this case, we observed that one advantage of the procedure performed via transperitoneal access was the possibility of access to the two kidney units, with no need for repositioning the patient.…”
Section: Discussionmentioning
confidence: 70%
“…1 With regard to adult cystic disease, the role of ablative laparoscopy is mainly related to renal decortication surgery for the relief of pain and symptoms related to large kidney volumes (dyspepsia, respiratory restrictions). 3 It yields one-year symptom remission rates that vary from 80 to 92%. 1 Nephrectomy is indicated in cases of hardto-control hypertension, recurring pyelonephritis and substantial protein loss in the urine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations